Consumers' perceptions of H&M's sustainability initiatives - Medved, Oleksandra; Martínez Pantoja, Yadira Ixchel; San José Iglesias, Rafael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
In response to raising environmental concerns and customers’ demand for corporate accountability, many fashion brands have taken up initiatives to promote sustainability. This bachelor's thesis investigates how consumers see fast fashion giant H&M's sustainability initiatives. It combines a quantitative survey measuring consumer awareness and attitudes with a qualitative content analysis of H&M's 2024 Sustainability Report and related greenwashing lawsuit. Consumers’ responses were analysed using descriptive statistical methods such as mean and standard deviation. The results indicate that although most H&M consumers are aware of the company's sustainability initiatives, they have doubts about how genuine they are. Notably, most of the respondents thought that environmental transparency and ethical labour standards were the most crucial, but they were also the most questioned. The paper identifies a gap between consumers' perceptions and company messaging about sustainability practices.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses